Identifying determinants of match performance in Division I women`s collegiate soccer players - Binns, J. T. (Electronic Theses and Dissertations, 3106, 2009)
The United States Olympic Committee (USOC) changed their funding strategy after the 2000 Olympic Games in Sydney, Australia. The USOC moved to a performance based funding strategy to focus on the bottom line and medal podium performance. After eight years of claiming to be an organization focused on performance based funding principles, monetary gains have been made while continuing to focus on the development of Olympic medalists. Clearly performance based funding principles have helped the USOC accomplish its stated goals. The purpose of this study was to determine if the USOC had embraced the fundamental principles of performance based funding and used them in their development of National Governing Body (NGB) high performance plans and goal establishment. How the principles of a performance based funding strategy fit with an organization like the USOC, was the overarching research question developed for this study. A case study using the documents from 10 different National Governing Bodies (NGBs) was used to determine the fit of performance based funding strategies and the USOC. Performance indications such as medal performance and overall financial standing of the USOC were also considered in answering the research questions.